1895 Mich. Pub. Acts 596 - (:unkn) unknown (My University, 1895)
Local Acts, § 44: Prohibited firing or discharging any gun or pistol, or carry of firearms, throwing of stones or other missiles within Bell Isle Park or boulevard
Keywords: DISCHARGE; SENSITIVE PLACES